Sum and Product of Roots

Slides:



Advertisements
Similar presentations
Roots of quadratic equations Investigating the relationships between the roots and the coefficients of quadratic equations.
Advertisements

10-7 The Quadratic Formula
7-5 solving quadratic equations
Using the Zero-Product Property to Solve a Quadratic
solution If a quadratic equation is in the form ax 2 + c = 0, no bx term, then it is easier to solve the equation by finding the square roots. Solve.
Quadratic Equations Sum and Product of the Roots.
Many quadratic equations can not be solved by factoring. Other techniques are required to solve them. 7.1 – Completing the Square x 2 = 20 5x =
7.1 – Completing the Square
EXAMPLE 4 Choose a solution method Tell what method you would use to solve the quadratic equation. Explain your choice(s). a. 10x 2 – 7 = 0 SOLUTION a.
4.8: Quadratic Formula HW: worksheet
6.5 – Solving Equations with Quadratic Techniques.
©G Dear2008 – Not to be sold/Free to use
Solving Quadratic Equations Using Completing the Square and the Quadratic Formula.
Goals: To solve quadratic equations by using the Quadratic Formula.
Algebra 9.5 Solving Quadratic Equations Using the Quadratic Formula This is an important section as there are many questions on the STAR test about the.
The Quadratic Formula. What does the Quadratic Formula Do ? The Quadratic formula allows you to find the roots of a quadratic equation (if they exist)
Quadratics Solving equations Using “Completing the Square”
Pre-Calculus Section 1.5 Equations Objectives: To solve quadratics by factoring, completing the square, and using the quadratic formula. To use the discriminant.
5.5 – The Quadratic formula Objectives: Use the quadratic formula to find real roots of quadratic equations. Use the roots of a quadratic equation to locate.
Roots of Polynomials Quadratics If the roots of the quadratic equation are  and  then the factorised equation is : (x –  )(x –  ) = 0 (x –  )(x –
4.8 Do Now: practice of 4.7 The area of a rectangle is 50. If the width is x and the length is x Solve for x by completing the square.
5.3 – Solving Quadratic Equations by Factoring. Ex. 1 Solve y = x 2 + 5x + 6 by factoring.
Lecture 301 Solving Quadratic Equations Two Methods Unit 4 Lecture 30 Solving Quadratic Equations.
WARM UP Find the product. 1.) (m – 8)(m – 9) 2.) (z + 6)(z – 10) 3.) (y + 20)(y – 20)
9.5 - The Quadratic Formula
Solve by factoring. x² = - 4 – 5x 2,. Solve by factoring. n² = -30 – 11n -4 and -1.
1.3 Quadratic Equations College Algebra: Equations and Inequalities.
Chapter 10 Section 1 Square Root Property. Learning Objectives Know that every positive real number has two square roots. Solve quadratic equation using.
Chapter 4: Polynomial and Rational Functions. 4-2 Quadratic Equations For a quadratic equation in the form ax 2 + bx + c = 0 The quadratic Formula is.
Aim: How do we solve quadratic equation with complex roots? Do Now: 1. Solve for x: 2. Solve for x: 3. Solve for x: HW: p.219 # 6,8,10,12,14 p.241 # 6,14,25.
Warm Up 1.) What is the graph of the function y = -x 2 + 4x + 1?
Title: ch. 6 Algebra: quadratic equations. Learning Objective: WALT solve quadratic equations by using the quadratic formula. p.143.
Warm Up  1.) Write 15x 2 + 6x = 14x in standard form. (ax 2 + bx + c = 0)  2.) Evaluate b 2 – 4ac when a = 3, b = -6, and c = 5.
AS Mathematics Algebra – Quadratic equations. Objectives Be confident in the use of brackets Be able to factorise quadratic expressions Be able to solve.
The Quadratic Formula The Quadratic Formula can be used to solve any quadratic equation that is in the form ax2 ax2 + bx bx + c = 0 I’ll have to write.
3.4 Chapter 3 Quadratic Equations. x 2 = 49 Solve the following Quadratic equations: 2x 2 – 8 = 40.
Lesson 6.5: The Quadratic Formula and the Discriminant, pg. 313 Goals: To solve quadratic equations by using the Quadratic Formula. To use the discriminant.
2.2 Solving Quadratic Equations Algebraically Quadratic Equation: Equation written in the form ax 2 + bx + c = 0 ( where a ≠ 0). Zero Product Property:
Section 5-8 A quadratic equation written in standard form ax 2 + bx + c = 0 can be solved with the Quadratic Formula:
SOLVING QUADRATIC EQUATIONS BY COMPLETING THE SQUARE
The Quadratic Formula..
Sec. 5-8: Quadratic Formula
4.6 Quadratic formula.
Discriminant and Quadratic
Aim: What are the properties of a quadratic equation?
The Quadratic Formula..
Forming a Quadratic Equation with Given Roots
Quadratic Formula Solving for X Solving for quadratic equations.
Sum and Product of Roots
Solve Quadratic Equations by the Quadratic Formula
4.6 Quadratic formula.
Algebra 1 Section 12.5.
5.6 – The Quadratic Formula And Ch 5 Review
SOLVING QUADRATIC EQUATIONS USING THE FORMULA
The Quadratic Formula.
Solving Quadratics by Factoring
Algebra 12.4 Completing the Square.
Review: Simplify.
Solving Quadratic Equations
Quadratic Equations.
9.2 Solving Quadratic Equations using square roots
Solving Quadratic Equations
Algebra 2 10/19/16 EQ: How do I complete the square to solve for x
Solve Quadratics by Graphing ax2 +bx + c
Warm-up  .
The Quadratic Formula..
The Quadratic Formula..
quadratic formula. If ax2 + bx + c = 0 then
Presentation transcript:

Sum and Product of Roots Quadratic Functions Sum and Product of Roots

Purpose Find sum/product of roots without knowing the actual value of x. Use the sum/product of roots to solve for other results

Derivation of Formula Given α and β are roots of a quadratic equation, we can infer that x1 = α and x2 = β , where α and β are just some numbers. For example, x2 – 5x + 6 = 0 has roots α and β  means that α = 2 and β = 3

However… Sometimes, we do not need the values of x to help us solve the problem. Knowing the relationship between the quadratic equation and its roots helps us save time

Derivation of Formula This tells us that: (x – α)(x – β) = 0 ax2 + bx + c = 0 has roots α and β –(1) This tells us that: (x – α)(x – β) = 0 Expanding, we have: x2 – αx – βx + αβ = 0 x2 – (α + β)x + αβ = 0 So, if we compare the above with (1): x2 + x + = 0 Result: αβ = , α + β =

In other words… x2 – (α + β)x + αβ = 0 ax2 + bx + c = 0 has roots α and β x2 – (α + β)x + αβ = 0 x2 – (sum of roots)x + product of roots = 0

Application – Example 1 (TB Pg 55) 2x2 + 6x – 3 = 0 has roots α and β, find the value of (a) Without finding α and β, we know the value for α + β and αβ α + β = – 3 and αβ = – 3/2 Hence,

Application – Example 1 (TB Pg 55) 2x2 + 6x – 3 = 0 has roots α and β, find the value of (b) We already know that: α + β = – 3 and αβ = – 3/2 Expanding (b), we have

Application – Example 2 (TB Pg 55) x2 – 2x – 4 = 0 has roots α and β, find the value of (a) Step 1: α + β = 2 and αβ = – 4 To find (a), we use the algebraic property Rearranging:

Application – Example 2 (TB Pg 55) x2 – 2x – 4 = 0 has roots α and β, find the value of (b) Step 1: α + β = 2 and αβ = – 4 To find (b), we use the algebraic property Rearranging: Hence, α − β =

Application – Example 2 (TB Pg 55) x2 – 2x – 4 = 0 has roots α and β, find the value of (c) Step 1: α + β = 2 and αβ = – 4 To find (a), we use the algebraic property Rearranging:

Application – Example 3 (TB Pg 56) 2x2 + 4x – 1 = 0 has roots α and β, form the equation with roots α2 and β2 Remember! x2 – (sum of roots)x + product of roots = 0 x2 – (α2 + β2)x + α2β2 = 0 So in order to get the equation, I must find α2 + β2 and α2β2 How?